Overview of U.S. peach breeding and production - Chunxian Chen (Technology in Horticulture)
Peach is an introduced crop with a relatively short history in the U.S., where dozens of public and private breeding programs have released hundreds of peach cultivars and successfully helped establish considerable production in many states. This paper provides a glimpse of U.S. peach breeding and production. Most public and private peach breeding programs have been terminated over the past decades or are currently being phased out, active breeding programs will continue releasing new improved peach cultivars and rootstocks to produce attractive nutrient-rich fruit for consumers. The declining trend in U.S. peach acreage and production suggests imminent challenges and issues facing the industry and demands continuous visionary breeding and horticultural research to find solutions for the sustainability and profitability of the U.S. peach industry.